ANALYSIS OF THE INTERACTION BETWEEN TEACHER AND STUDENTS IN ENGLISH SPEAKING SKILL AT SMK NEGERI 1 GIDO - Jumidar Halawa; Adieli Laoli; Kristof Martin Efori Telaumbanua; Riswan Zega (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study was conducted to describe classroom interaction in learning English as a foreign language in X (Ten) Grade at SMK Negeri 1 Gido. Specifically, this study aims to determine the proportion and pattern of classroom interaction through Flanders Interaction Analysis Categories System (FIACS) analysis and the barriers to classroom interaction in learning English. This study used a mixed-method research method, and data were obtained using direct observation and interviews. The results showed that teacher talk dominated classroom interaction, which amounted to 59.39% in three meetings. As for the interaction patterns that occur, a multi-directional interaction pattern is the most dominant, where teachers and students can each interact and provide feedback between teachers and students. In addition, teacher also experienced several barriers in classroom interactions, namely difficulties in dealing with overactive students, feeling confused when the learning process takes place, confusion in choosing learning methods that suit students' learning styles, lack of mastery of skills, too many students in one class, and limited learning time. Meanwhile, students also experienced several barriers during classroom interactions, including difficulties in speaking and understanding teacher explanations, lack of confidence in their ability to remember new vocabulary, ineffective classroom atmosphere, lack of speaking and communication practice, and different ways of pronouncing and writing in English